A Comprehensive Review of Exopolysaccharides From Lactic Acid Bacteria: Production, Characterization, and Applications in Food and Health - Hafsa Arshad; Rao Mubashar Ali; Shahgull; Sahar Fazal; Aqsa Qasim Zafar; Laiba Mahmood; Mishal; Muhammad shoaib (Biotechnology and Applied Biochemistry, 2026)
ABSTRACT Lactic acid bacteria (LAB) produce exopolysaccharides (EPSs), which are beneficial in food and health applications because of their varied structural and functional characteristics. These EPSs are attracting a lot of interest. Homopolysaccharides (HoPSs) and heteropolysaccharides (HePSs) are two types of LAB‐derived EPS that differ in their monosaccharide compositions and physicochemical properties. These biopolymers are produced through processes, such as extracellular synthesis and Wzx/Wzy‐dependent mechanisms, which are controlled by environmental and genetic variables like pH, temperature, fermentation duration, and carbon‐to‐nitrogen ratios. In dairy products, like yogurt and cheese, EPS improves texture, moisture retention, and shelf life by acting as natural thickeners, stabilizers, and emulsifiers. They are also perfect for clean‐label formulations due to their biocompatibility and biodegradability. In addition to its use in food, EPS has anticancer, antioxidant, immunomodulatory, cholesterol‐lowering, and antidiabetic benefits. They alter gut microbiota, enhance intestinal health, and interact with immunological receptors (such as toll‐like receptors [TLRs]). Furthermore, EPS exhibits promise in medicinal applications like biofilm inhibition, wound healing, and drug delivery systems. Large‐scale applications are restricted by issues including low yield and high manufacturing costs, notwithstanding their potential. To overcome these obstacles, developments in genetic engineering and fermentation optimization are essential. The biosynthesis, structural variety, and multifunctional roles of LAB‐EPS in food innovation and health promotion are highlighted in this review, which also highlights future research areas to increase their industrial and therapeutic value.